2022
DOI: 10.22216/jen.v6i1.137
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Uji Korelasi Pearson, Spearman Dan Kendall Tau Dalam Menganalisis Kejadian Diare

Abstract: Diarrhea is one of the infectious diseases that are commonly found in the Selayo community, Solok Regency. The purpose of this study was to find out the analysis of Pearson correlation test, spearman, control of the incidence of diarrhea in the work area of the Selayo Community Health Center. This type of research is Analytical survey with cross sectional study design using a non-reactive approach. The study population was the entire population in Nagari Salayo of 43,043 people from 22 jorong. Diarrhea inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…UI. 4 The [17], [18]. The findings of this validity test will assist in determining how reliable the questions in this study are in evaluating students' interest and motivation, as well as if the relationship between interest, motivation, and mBlock interface design adheres to the study's assumptions.…”
Section: Ui2mentioning
confidence: 96%
“…UI. 4 The [17], [18]. The findings of this validity test will assist in determining how reliable the questions in this study are in evaluating students' interest and motivation, as well as if the relationship between interest, motivation, and mBlock interface design adheres to the study's assumptions.…”
Section: Ui2mentioning
confidence: 96%
“…<0.05, it can be concluded that there is a significant correlation between variables, and H_1 is accepted if sig. > 0.05, it can be concluded that there is no significant correlation between variables [15], [16]. This test aims to test whether there is an influence between the satisfaction variable on the safety and comfort variable by using software in the form of the SPSS version 25 application.…”
Section: Correlation Testmentioning
confidence: 99%
“…Uji korelasi yaitu pola atau metode statistik untuk mengetahui korelasi dua variabel atau lebih dimana hal tersebut diukur variabel atau lebih dari satu. Hasil dinyatakan sebagai koefisien korelasi mulai dari -1 sampai 1, dengan nilai 0 menunjukkan tidak ada hubungan (Yanti & Akhri, 2021) Rata-rata sales (dengan jumlah data 40 buah ) adalah Rp. 248,20 juta dengan standar deviasi Rp 40.878 juta.…”
Section: Hasil Dan Pembahasan Analisis Deskriptif Dan Correlationsunclassified